2011
DOI: 10.1186/1471-2458-11-732
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of proactive telephone counselling for smoking cessation in parents: Study protocol of a randomized controlled trial

Abstract: BackgroundSmoking is the world's fourth most common risk factor for disease, the leading preventable cause of death, and it is associated with tremendous social costs. In the Netherlands, the smoking prevalence rate is high. A total of 27.7% of the population over age 15 years smokes. In addition to the direct advantages of smoking cessation for the smoker, parents who quit smoking may also decrease their children's risk of smoking initiation.Methods/DesignA randomized controlled trial will be conducted to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Outcomes among children will be examined in a separate report. More detailed information regarding all aims and research questions of this trial can be found in the study protocol [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes among children will be examined in a separate report. More detailed information regarding all aims and research questions of this trial can be found in the study protocol [21].…”
Section: Methodsmentioning
confidence: 99%
“…All participants provided written informed consent. The study is registered in the Netherlands Trial Register (NTR2707) and the full study protocol is publicly available [21]. The baseline measurement took place between January and July 2011.…”
Section: Study Overviewmentioning
confidence: 99%
“…In addition, children received 10 euro (approximately 13 US dollars) for participation in the fourth assessments. Full reports of the study design, the recruitment procedure, and treatment effects among parents have been published elsewhere (Schuck, Otten, Kleinjan, Bricker, & Engels, 2011Schuck et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For the present study, only the parent data were used. More detailed information regarding the use of the child data can be found in the study protocol [32]. After the baseline assessment, parents were randomly assigned to either the telephone counselling condition (n=256) or the self-help brochure condition (n=256).…”
Section: Methodsmentioning
confidence: 99%